FEATURES OF INSTITUTIONAL SUPPORT AND PROMOTE SMALL BUSINESS DEVELOPMENT ABROAD - I. Kuznetsov (Вестник университета, 2016)
The article is devoted to the support of small enterprises in foreign countries, which is one of the key challenges facing the nation. Many countries have established a comprehensive and effective system of incentives and regulation of small businesses. This system allows you to have a multilateral impact on the functioning of small businesses using various means and methods, and its improvement and adaptation to changing conditions is a strategic priority of the state.